Bioactive-Glass-Incorporated Plasma Electrolytic Oxidation Coating on AZ31 Mg Alloy: Preparation and Characterization - Syed Ahmed Uzair; Fayaz Hussain; Muhammad Rizwan (Ceramics)
Magnesium alloys, despite having a number of attractive properties, encounter difficulties in clinical applications due to their rapid degradation rate in the physiological environment. In this work, a Bioglass (BG)-incorporated plasma electrolytic oxidation (PEO) coating was applied on the AZ31 Mg alloy to overcome this major limitation. PEO treatment was carried out in constant current mode with and without the addition of BG particles. The effects of BG particles on the coating’s morphology, composition, adhesion, electrochemical corrosion resistance and bioactivity were analyzed. SEM micrographs revealed that BG submicron particles were well adhered to the surface and the majority of them were entrapped in the micropores. Furthermore, the adhesion strength of the coated layer was adequate—a maximum value of 22.5 N was obtained via a micrometer scratch test. Potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) results revealed that the degradation rate of the Mg alloy was slowed down by up to 100 times, approximately. Moreover, the PEO–BG layer considerably enhanced the in vitro bioactivity of the Mg alloy in a simulated body fluid (SBF) environment; a prominent apatite layer was witnessed through SEM imaging. Consequently, the BG-incorporated PEO layer on Mg AZ31 alloy exhibited some promising outcomes and, therefore, can be considered for biomedical applications.